Performance of a scintillator-based ion detector for CRYRING@ESR. Issue 23 (January 2020) - Menz, E B; Hahn, C; Pfäfflein, P; Weber, G; Stöhlker, Th
Synopsis: A detector based on the scintillator material YAP:Ce and capable of counting single ions is present-ed. The detector consists of a YAP:Ce crystal and a light guide operating in ultra high vacuum and a convention-al photomultiplier outside the vauum. The crystal demonstrated the necessary radiation hardness against heavy ion irradiation. The detector has been commissioned at CRYRING@ESR and its detection capabilities have been confirmed with beam from the local source.